LITERASI MANUSIA, SOSIAL DAN RELIGIUS DALAM MENGHADAPI ERA INDUSTRI 4.0 DAN ERA MASYARAKAT 5.0 HUMAN, SOSIAL AND RELIGIUS LITERACY IN FACING THE INDUSTRY ERA 4.0 AND SOCIETY ERA 5.0 - Keristian Dahurandi (Jurnal Alternatif Wacana Ilmiah Interkultural, 2022)
Digital literacy, as emphasized in the industrial era 4.0 and society era 5.0, still cannot fully provide right solution to overcome negative impacts on humanity. Digital literacy should take ethical aspect of humanity into account in the development and use of technology. In fact, digital technology actually instrumentalizes humans as key-entrance to interacting in this current era. Through the industry 4.0 and society 5.0 eras, humans are directed to be digitally intelligent in order to have leadership qualities, digital literacy, communication, emotional intelligence, entrepreneurship, global insight, problem solving, and able to work in groups. Emphasis on some of these things ignores the consideration of humans as complex beings who also need to separate from moving on through technological systems. The results of the study show that there are times when humans should not be connected to the contexts of other life, but relate intra-personally. Therefore, by reviewing various literatures on hand, it is found that there are at least three things that a person should pay attention to in facing the society era 5.0, namely human literacy which strengthens humans personally, sosial literacy which strengthens humans sosial ly with other humans and religious literacy that strengthens humans whose existence must depend on the cosmos or the universe and The God.